SUCCESSFUL APPLICATION OF PERIPHERAL VENO-ARTERIAL EXTRACORPOREAL MEMBRANE OXYGENATION FOR CARDIAC ALLOGRAFT ANTIBODY-MEDIATED REJECTION WITH SEVERE HEMODYNAMIC COMPROMISE - V. N. Poptsov; E. A. Spirina (Вестник трансплантологии и искусственных органов, 2015)
Introduction. Acute antibody-mediated rejection (AMR) is one of the severe complications of early and late period after heart transplantation (HT). Only few case reports and studies presented of mechanical circulatory support (MCS) application for refractory acute rejection causing hemodynamic compromise. Aim. We report the case of a woman with cardiogenic shock caused by severe AMR that was successfully treatment by peripheral venoarterial extracorporeal membrane oxygenation (VA ECMO). Material and methods. In december 2014, a 60-year-old woman with dilated cardiomyopathy was operated for HT. The patient had a good initial cardiac allograft function and no and was discharged from ICU on the 4th day after HT. 1st endomyocardial biopsy (EMB) (the 7th day after HT) showed absence of acute cellular and antibody-mediated rejection. On the 11th day after HT patient aggravated and presented clinical signs of life-threatening acute cardiac allograft dysfunction: arterial blood pressure 78/49/38 mm Hg, HR 111 in min, CVP 20 mm Hg, PAP 47/34/25 mm Hg, PCWP 25 mm Hg, CI 1.5 l/min/m2, adrenalin 110 ng/kg/min, dopamine 15 mcg/kg/min. ECG showed impairment of systolic left (LVEF 25%) and right (RVEF 15%) ventricle function, left and right ventricle diffuse hypokinesis, thickness of IVS, LV and RV wall 1.7, 1.4 and 0.8 cm, tricuspid and mitral valve regurgitation 2–3 degrees. EMB presented AMR. In conscience peripheral VA ECMO was installed. We used peripheral transcutaneous cannulation technique via femoral vessels – arterial cannula 15 F, venous cannula – 23 F, vascular catheter 14 G for anterograde leg’s perfusion. ACT 130–150 sec. AMR therapy included: methylprednisolon pulse-therapy (10 mg/kg for 5 day), IgG, plasmapheresis (No 7), rituximab. Results. Under MCS by VA ECMO we noted quick improvement of hemodynamic, metabolic homeostasis and organ functions. On the 6th day of VA ECMO (blood flow 1.8 l/min): arterial blood pressure 133/81/54 mm Hg, CVP 5 mm Hg, PAP 31/21/12 mm Hg, PCWP 12 mm Hg, CI 3,4 l/min/м2, HR 85 in min, LVEF 53%, IVS 1.3 cm, mitral valve regurgitation <1 degree, inotropic support was discontinued. Control EMB showed resolution of AMR. Duration of VA ECMO was 7 days. Patient was discharged from ICU on the 2nd and 26th day after VA ECMO in stable clinical status. Conclusion. VA ECMO should be crucial component of treatment of cardiac allogaft antibody-mediated rejection with severe hemodynamic compromise.